Electron beam irradiator for post-harvest processing of chestnut fruits: technical parameters and feasibility - Antonio, Amilcar L. (2014)
In a recent worldwide estimation, food irradiation processing represents about 400 000 ton, from which almost half (186 000 ton) were to eliminate insects. In EU Mediterranean countries chestnut fruits production represents a market of more than 100 000 ton, being Portugal the third producer with an amount of 20 000 ton, exporting 25% of the production, representing an income of about 15 million Euros. In March 2010, a European Union commission decision prohibited the use of methyl bromide (MeBr), a wide spectrum fumigant used for different agricultural purposes, namely for post-harvest disinfestation of chestnut fruits. The banning of MeBr could represent an opportunity to implement ionizing radiation treatment, as a well tested technology in other food commodities for post-harvest preservation. Electron beam irradiators are more hardware sophisticated than gamma irradiators, however due to several factors they are becoming more popular and being the first choice, whenever the product can be treated by low penetration radiation. Since the current focus for food irradiation is in e-beam versatility and advantages, it is presented in this paper a detailed analysis and discussion about technical characteristics and feasibility for post-harvest irradiation of chestnut fruits, taking in account the physical dimensions and fruits seasonality, beam energy, throughput and total costs of operation, to estimate the impact on the final price of the irradiated product.